2019
DOI: 10.3389/fnagi.2019.00092
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Intervention for People With Dementia and Their Partners: Results of a Mixed-Methods Study

Abstract: Objective Studies have shown preliminary support for mindfulness-based interventions benefitting people with dementia and their caregivers. However, most studies focus on these two groups separately. This study examined whether it would be possible and beneficial for people with dementia and their caregiver to jointly undergo an adjusted Mindfulness-Based Stress Reduction (MBSR) training, named TANDEM. Methods The 8-week MBSR training was adjusted based on a literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…Most of them were women caregivers of persons with dementia. The mean sample age varied from 46, specifically, in the study by Franco et al [30] and 70 in the study done by Berk et al [15]. The time employed in the mindfulness-based interventions varied from one study to another.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of them were women caregivers of persons with dementia. The mean sample age varied from 46, specifically, in the study by Franco et al [30] and 70 in the study done by Berk et al [15]. The time employed in the mindfulness-based interventions varied from one study to another.…”
Section: Resultsmentioning
confidence: 99%
“…For example, for depression, the study which showed the least effect was the one by Waelde and Gallagher-Thompson [23] on anxiety, the intervention by Whitebird et al [17] and for perceived stress, the study by Oken et al [33]. For caregiver burden, it was the study by Berk et al [15], and, finally, for the sleep quality variable, it was the work by Oken et al [33]. However, the results of the meta-analysis by subgroup showed that the interventions had a significant (p ≤ 0.00001) effect, with an SMD at a Confidence Interval (CI) of 95% = 0.71 (0.52, 0.89).…”
Section: Results Variables For Depression Anxiety Perceived Stress mentioning
confidence: 99%
See 2 more Smart Citations
“…This written, encouraging feedback from peers is used to enhance the learning of both the reviewers and the authors, to deepen their thinking, and to foster their reflection [56,64]. In addition, shared experiences with peers give emotional support and can have multiple positive effects on well-being [55,94]. For this reason, we implemented group work and discussion to the course.…”
Section: Discussionmentioning
confidence: 99%